Sob vigilância: o equilíbrio entre segurança e privacidade na gestão de dados pelo Estado brasileiro - Barros, Kelviane de Assunção Ferreira (2023)
This study explores personal data collection, storage, processing and use by Public Authorities in Brazil in the context of public security, emphasizing the implications of these practices in the scenario of fundamental rights. Through a historical analysis and contemporary casesstudy, this dissertation investigates the evolution of personal data management by public administration, highlighting the need for a careful approach when handling this data. Examining the current legal regime under the General Data Protection Law, the work critically evaluates the effectiveness of existing regulations and their application in the administrative and judicial spheres. Practical cases that illustrate the application of data protection standards in Brazil are also discussed, providing a critical view of the legislation and its execution. Based on these studies, the dissertation proposes improvements in the management of personal information, suggesting technical methods and procedures for more effective data protection that respects fundamental rights. In the end, the study aims to establish recommendations for improving the regulation of the use of personal data by the Public Authorities within public security scope, ensuring the preservation of the fundamental rights of citizens in the national territory.